Association of soluble transferrin receptor/log ferritin index with all-cause and cause-specific mortality: National Health and Nutrition Examination Survey - Yu, Yan; Lu, Dongying; Zhang, Zhenhui; Tao, Lili (Frontiers in Nutrition, 2024)
Background Soluble transferrin receptor (sTfR)/log ferritin index (sTfR Index) can be used to assess the entire spectrum of iron status, and is valuable in evaluating iron status in population studies. There is still a lack of evidence on the association between sTfR index and all-cause mortality.Object To explore the association between sTfR index and all-cause mortality, as well as mortality due to cardiovascular disease (CVD) and cancer.Method Data were from the National Health and Nutrition Examination Survey (NHANES) between 2003 to 2020. Participants aged 16 years and older who had complete data of serum ferritin and sTfR were included. Pregnant individuals or those with ineligible data on death or follow-up were excluded from the analysis. Baseline sTfR index was calculated by baseline sTfR/log(ferritin) and classified as three tertile. We performed the Cox proportional hazard regression to assess the association of sTfR index (both continuous and categorical scale) with all-cause and cause-specific mortality and further assess the non-linear relationship between sTfR index and the outcomes with restricted cubic spline.Result In this study, 11525 participants, a total of 231 (2.0%) all-cause deaths occurred during a median follow-up of 51 months. The risk of all-cause mortality, CVD-related mortality, and cancerrelated mortality was higher in participants with highest tertile of sTfR index. After confounding factors adjustment, participants with highest tertile of sTfR index were associated with an increased risk of all-cause mortality (HR, 1.71; 95%CI, 1.14-2.57) as compared with lowest tertile. Additionally, sTfR index per SD increment was associated with a 25% increasing risk of all-cause mortality (HR:1.25, 95%CI:1.08-1.45, P=0.003) and a 38% cancer-related mortality (HR:1.38, 95%CI:1.07-1.77, P=0.018). These associations remained robust after adjusting for the serum ferritin as well as in various subgroups stratified by age, sex, smoking statue, hypertension, diabetes, and CVD. Spline analysis showed that there is approximately linear relationship between sTfR index with all-cause mortality (P for non-linear=0.481). Moreover, ferritin was not a predictor of all-cause death after adjustment for confounding factors.Significance This cohort study demonstrated a significant association between sTfR index increment and an increased risk of all-cause and cancer-related mortality, independent of ferritin levels.